The Effects of Memorizing the Qur'an toward Students' Attitude in Elementary School - Iswandi, Iswandi; Febrian, St. Ade Moon; Akmal, Fauzi; Duryat, Masduki; Sriwardona, Sriwardona; Siregar, Irma Suryani; Albizar, Albizar (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
One of the miracles of the Alquran has been proven to impact the behavior of individuals who memorize it. Memorizing the Alquran must start as a child. Alquran memorization programs in elementary schools have been started in several regions in Indonesia. Still, research needs to be carried out regarding the success and effects of this program on students. This research aims to analyze the effect of memorizing the Alquran on the behavior of students in elementary schools. This research uses a qualitative method with a case study approach, data sources were taken through individual and group interviews with seven informants who were selected using the technique of purposive sampling, The informants are school principals, teachers, and students. All data was analyzed thematically using the Milles and Huberman interactive analysis technique. The research findings show that students in elementary school memorizing the Alquran are doing well according to the desired goals because the entire program is carried out starting with good planning, a process that is by the goals prepared, and ongoing evaluation. Regarding the effect of memorizing the Alquran on students' positive behavior, the findings prove three changes in students' behavior, i) speaking softly, ii) using more time to read the Alquran, and iii) being more respectful towards teachers. These findings have succeeded in revealing that memorizing the Alquran can change students' behavior in a positive direction this program can be used as an example by other schools as a platform for moral education in elementary schools.